Does the lack of financial stability impair the transmission of monetary policy? - Viral V. Acharya; Björn Imbierowicz; Sascha Steffen; Daniel Teichmann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
We investigate the transmission of central bank liquidity to bank deposits and loan spreads in Europe over the January 2006 to June 2010 period. We find evidence consistent with an impaired transmission channel due to bank risk. Central bank liquidity does not translate into lower loan spreads for high-risk banks, even as it lowers deposit rates for both high-risk and low-risk banks. This adversely affects the balance sheets of high-risk bank borrowers, leading to lower payouts, lower capital expenditures, and lower employment. Overall, our results suggest that banks' capital constraints at the time of an easing of monetary policy pose a challenge to the effectiveness of the bank lending channel and the effectiveness of the central bank as a lender of last resort.
urn:nbn:de:hebis:30:3-480571
Keywords: E43; E58; G01; G21; 330; Central bank liquidity; Monetary policy transmission; Corporate deposits; Financial crisis; Lender of last resort; Banking crisis; Loans; Real effects